How do mobile health applications support behaviour changes? A scoping review of mobile health applications relating to physical activity and eating behaviours. (October 2019) - Aromatario, O.; Van Hoye, A.; Vuillemin, A.; Foucaut, A.-M.; Crozet, C.; Pommier, J.; Cambon, L.
Abstract: Objective: The objective of this review was to analyse how researchers conducting studies about mobile health applications (MHApps) effectiveness assess the conditions of this effectiveness. Study design: A scoping review according to PRIMSA-ScR checklist. Methods: We conducted a scoping review of efficacy/effectiveness conditions in high internal validity studies assessing the efficacy of MHApps in changing physical activity behaviours and eating habits. We used the PubMed, Web of Science, SPORTDiscus and PsycINFO databases and processed the review according to the O'Malley and PRISMA-ScR recommendations. We selected studies with high internal validity methodologies (randomised controlled trials, quasi-experimental studies, systematic reviews and meta-analyses), dealing with dietary and/or physical activity behaviours; covering primary, secondary or tertiary prevention and dealing with behaviour change (uptake, maintenance). We excluded articles on MHApps relating to high-level sport and telemedicine. The process for selecting studies followed a set protocol with two authors who independently appraised the studies. Results: Twenty-two articles were finally selected and analysed. We noted that the mechanisms and techniques to support behaviour changes were poorly reported and studied. There was no explanation of how these MHApps work and how they could be transferred or not. Indeed, the main efficacy conditions reported by authors refer to practical aspects of the tools. Moreover, the issue of social inequalities was essentially reduced to access to the technology (the shrinking access divide), and literacy was poorly studied, even though it is an important consideration in digital prevention. All in all, even when they dealt with behaviours, the evaluations were tool-focused rather than intervention-focused and did not allow a comprehensive assessment of MHApps. Conclusion: To understand the added value of MHApps in supporting behaviour changes, it seems important to draw on the paradigms relating to health technology assessment considering the characteristics of the technologies and on the evaluation of complex interventions considering the characteristics of prevention. This combined approach may help to clarify how these patient-focused MHApps work and is a condition for improved assessment of MHApps in terms of effectiveness, transferability and scalability. Highlights: This review identified five practical conditions influencing the effectiveness of mobile health applications (MHApps) used in prevention. It showed limitations with regard to process evaluation to clarify whether or not a MHApps could support behaviour change. This new analytical approach may help clarify how health-related MHApps are assessed and in particular prevention MHApps that are patient-focused. A particular finding was that most MHApps had been analysed as tools rather than as prevention strategies. To draw on the paradigms related to health technology assessment and evaluation of complex interventions seems a way to reduce health inequalities.